2010
DOI: 10.1109/twc.2010.070710.090240
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Average BER in Multihop Wireless Networks over Fading Channels

Abstract: This paper addresses the problem of finding an analytical expression for the end-to-end Average Bit Error Rate (ABER) in multihop Decode-and-Forward (DAF) routes within the context of wireless networks. We provide an analytical recursive expression for the most generic case of any number of hops and any single-hop ABER for every hop in the route. Then, we solve the recursive relationship in two scenarios to obtain simple expressions for the end-to-end ABER, namely: (a) The simplest case, where all the relay ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 20 publications
1
62
0
3
Order By: Relevance
“…End to end ABER in multi hop Decode and Forward (DAF) routes within the WLAN by considering the Nakagamim fading channels with various modulation schemes like binary differential phase shift keying (DBPSK), 4-QAM ascribed in [24]. These are associated to a differentially coherent instead of the ideally coherent detection of 4-QAM in single and multi hop.…”
Section: Table1 Effect Of Nc Technique On Minimum Ber and Power Modumentioning
confidence: 99%
“…End to end ABER in multi hop Decode and Forward (DAF) routes within the WLAN by considering the Nakagamim fading channels with various modulation schemes like binary differential phase shift keying (DBPSK), 4-QAM ascribed in [24]. These are associated to a differentially coherent instead of the ideally coherent detection of 4-QAM in single and multi hop.…”
Section: Table1 Effect Of Nc Technique On Minimum Ber and Power Modumentioning
confidence: 99%
“…Due to the wireless nature of the signals, we consider Rayleigh fading and path loss attenuation. Finally, due to the wireless environment and following [4,5], we do not constrain the transmission range of each node to one hop, as done in [1][2][3].…”
Section: Network Modelmentioning
confidence: 99%
“…These networks have been the focus of an intense research in the recent years, where Multihop Communication has been shown to be an effective method for establishing connectivity between nodes of a network where direct transmission is not feasible due to coverage or battery life issues [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, numerous contributions addressed the performance of multihop relayed transmission. In [18], authors investigated the same performance problem of multihop relay link over different fading channels. A cascaded multihop framework is developed in [19].…”
Section: Introductionmentioning
confidence: 99%